Language Games and Their Importance in Developing Language Skills - Dalal Ahmed Saleh; Yusif Sharef Saeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research is part of a doctoral thesis entitled (Language games and their role in the language development of Kurdish children, Pirmam town as a sample). The title of the research is (language games and their importance in developing language skills). We have presented the definitions of several scientists and linguists in this field, and we have expressed our opinions in this regard. We have divided the types of language games into four types, namely listening, speaking, reading, and writing skills. For each of them, we have identified its definitions and importance, and we have presented several language games.